How the Money Supply and the Rupiah Exchange Rate Influenced Indonesia's Inflation Rate from 2017 to 2022 ? - Roshifa, Ade; Ramdani, Eggy Armand; Fani, Andifa Dwi; Nurani, Rani (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, INDONESIA, 2023)
The study aims to determine the effect of money supply on inflation, to determine the effect of rupiah exchange rate on inflation, and to determine the effect of the two variables on inflation in the period 2017-2022. This research is quantitative with inferential statistical methods and uses secondary data collected through literature studies. Data analysis includes Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test, and Determination Coefficient Test (R²). The results show that money supply does not have a significant effect on inflation (probability value 0.2839 > 0.05). In contrast, the rupiah exchange rate has a significant effect on inflation (probability value 0.0160 < 0.05). Simultaneously, these two variables have a significant influence of 8.96% on inflation.